Stock market returns and GDP growth - Ferdinand Fichtner; Heike Joebges (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2024)
The existing econometric evidence on the relationship between stock indices and real economic activity is inconclusive despite theoretical arguments suggesting a long-term relationship. Previous studies indicate that the link between stock prices and growth became weaker in the 1980s. In this paper, we revisit this issue for the period between 1991 and 2019, and address potential explanations for the decoupling. Specifically, we examine the asymmetric effects of stock index increases and decreases, consider the impact of foreign demand on the relationship, control for changes in factor income distribution, and incorporate long-term interest rates as a proxy for changes in discount rates. Our analysis suggests that the relationship between stock prices and GDP remains fairly unstable, with stronger evidence for a link in more recent periods of our sample. All in all, we find the long-run effect of a permanent one-percent change of stock prices on GDP to be around 0.2 percent. The effect mostly materializes within two to three years. Effects tend to be less pronounced and are slower to materialize for non-Anglo-Saxon economies and in the case of stock price decreases. – – Der Artikel analysiert die hohen Aktienmarktrenditen in G7 Ländern, die in mehreren Jahrzehnten über dem BIP-Wachstum lagen, obwohl theoretisch ein enger Zusammenhang zu erwarten ist. Untersucht wird in einem (asymmetrischen) Kointegrationsansatz ab 1991, ob strukturelle Veränderungen wie z.B. der Rückgang der Lohnquote zu der vermeintlichen Entkoppelung beigetragen haben.
Keywords: C53; E44; E47; G12; 330; macroeconomic fluctuations; financial markets; stock prices; ARDL bounds test; asymmetric cointegration; Macroeconomic fluctuations; financial markets; stock prices; ARDL bounds test; asymmetric cointegration; yield returns